KETERANGAN TESTIMONIUM DE AUDITU YANG DIJADIKAN SEBAGAI ALAT BUKTI DALAM PENJATUHAN PUTUSAN HAKIM - Putri, Filzah Arina; Mahyani, Ahmad (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
According to Article 1 point 26 of the Criminal Procedure Code, neither the Public Prosecutor nor Legal Counsel may present witnesses who are deemed to have met the requirements as qualified witnesses. According to Article 185 paragraph (6) letter a of the Criminal Procedure Code, one of the main factors that must be considered by the panel of judges in determining whether or not a witness’ statement is true or not is the conformity between the testimony of the first witness and the statements of other witnesses. This assessment is also inseparable from the judge’s conviction which will be determined by the evidence provided by the witness. Basically, the witness testimony de auditu cannot be said to be a valid witness or cannot be accepted as evidence in the evidentiary process. In the field of criminal law, the terms criminal and sentencing are used interchangeably. However, the term punishment is more precisely interpreted as "suffering that is intentionally imposed or given by the state to a person or several people as a legal consequence (sanction) for him for his actions that violate the prohibition of criminal law". Because almost all proof of criminal cases depends on examining witness evidence, witness testimony is very important in the process of proving a case in court. However, the judge still depends on the evidence presented, the court can consider everything related to the guilt or innocence of the defendant. Witness testimony is one of the means of evidence based on evidence regulated in Law Number 8 of 1981 concerning the Criminal Procedure Code (KUHAP). In handling criminal cases, evidence in the form of witness testimony has legal weight. The testimony of this witness is prioritized in the verification process and has the potential to be the most significant piece of evidence when the case is heard